2019
DOI: 10.3390/foods8120678
|View full text |Cite
|
Sign up to set email alerts
|

Technofunctional and Sensory Properties of Fermented Lupin Protein Isolates

Abstract: Lupin protein isolate was fermented with eight different microorganisms to evaluate the influence on sensory profile, techno-functional properties and protein integrity. All investigated microorganisms were able to grow in lupin protein isolate. The results showed that the foaming activity in the range of 1646–1703% and the emulsifying capacity in the range of 347–595 mL of the fermented lupin protein isolates were similar to those of the unfermented ones. Protein solubility at pH 4 showed no significant chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 30 publications
5
51
0
Order By: Relevance
“…Fermentation of pea flour, soy and lupin protein isolates has shown similar effects on the protein solubility in other studies ( Cabuk et al., 2018 ; Kumitch et al., 2020 ; Meinlschmidt et al, 2016b ; Schlegel et al., 2019 ). The decline of protein solubility by fermentation might be related to different factors such as 1) changes in the protein surface, leading to exposure of hydrophobic groups and protein-protein interactions, 2) changes in the surface charge of the samples, and 3) increase in biomass due to microorganisms’ growth.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Fermentation of pea flour, soy and lupin protein isolates has shown similar effects on the protein solubility in other studies ( Cabuk et al., 2018 ; Kumitch et al., 2020 ; Meinlschmidt et al, 2016b ; Schlegel et al., 2019 ). The decline of protein solubility by fermentation might be related to different factors such as 1) changes in the protein surface, leading to exposure of hydrophobic groups and protein-protein interactions, 2) changes in the surface charge of the samples, and 3) increase in biomass due to microorganisms’ growth.…”
Section: Resultssupporting
confidence: 64%
“…A large part of the components responsible for the characteristic off-flavors of peas can be traced back to oxidation and enzymatic degradation products of unsaturated fatty acids during harvest, storage ( Roland, Pouvreau, Curran, van de Velde and de Kok, 2017 ) and further processing ( Azarnia et al., 2011 ; Heng et al., 2004 ; Lan et al., 2019 ). Fermentation has been widely used to improve sensory properties of different cereal and legume products ( Ferri et al., 2016 ; Kaczmarska et al., 2018 ; Meinlschmidt et al, 2016a ; Schlegel et al., 2019 ). During fermentation, biochemical changes occur, such as degradation and formation of organic substances developing a more intense aroma profile ( Adewumi, 2019 ; Cabuk et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…High survivability of kefir microflora in plant-based beverages was also reported [ 11 , 18 , 19 ]. Jimenéz-Martínez et al observed high LAB survivability in lupin milk [ 16 ], whereas Schlegel et al noted comparable survivability of different Lactobacillus strains in fermented lupin protein isolate [ 43 ]. However, values reported by Zaworska et al for fermented lupin seeds [ 40 ], are lower than reported in present study.…”
Section: Resultsmentioning
confidence: 99%
“…), bacteria ( Bacillus subtilis , Bifidobacterium sp., Lactobacillus sp., Pediococcus sp.) or spontaneously [ 27 , 39 , 40 , 41 , 42 , 43 ]. There are no studies available concerning lupin seeds fermented by kefir grains.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the lactic acid fermentation of faba bean flours has been demonstrated as a potential pretreatment for improvement of the nutritional quality of gluten-free faba breads, without affecting their sensory properties [ 7 ]. Schlegel et al [ 8 ] reported the fermentation of lupin protein isolated with up to eight different microorganisms, and the effects on the sensory and techno-functional (protein solubility, foaming and emulsifying capacity) properties, and the protein’s resistance to the fermentative process, were both evaluated. The fermentation of a pea protein solution with a starter culture of lactic bacteria and different yeasts significantly reduced the presence of green-off compounds; such results are of interest for the food industry in terms of increasing the acceptability of plant matrices to consumers [ 9 ].…”
mentioning
confidence: 99%